The Impact of 21st Century in Education as a Learning Revolution - Uci Dwi Cahya; Weni Astari; Hendra Susanto (LPPM Universitas Bumigora Mataram, 2023)
The study reveals to impact of 21st century education as a learning revolution. The research focus is directed at four sub variables; lesson planning; implementation of learning; learning assessment; and learning supervision. In this study, collecting data from various sources, the impact of 21st century education as a learning revolution are included in the category of several changes that must be made, such as: Planning the concept of conventional education; understanding education as an important part of efforts to create changes for better management of the life of the nation and state; Creating education that can adapt to the changing nature of globalization; Respond positively to the current changes in globalization and then direct them towards the concept of sustainable management, and create the concept of sustainable education. The results are expected to be input for other, regarding the real conditions in the field related to the impact of 21st century education as a learning revolution so that it can be taken into consideration in implementing the learning revolution in the 21st century. The impact of 21st century education in the learning revolution. This study is a literature review using a qualitative approach. Schools are part of the population in this study, and the sample uses a saturated sampling technique. Data were analyzed using a simple regression technique. The results of the study show that 90% of the impact of 21st century education influences the learning revolution. Positively changes in the flow of globalization then direct it to the concept of sustainable education management, thereby creating the concept of 21st century education.